Antigenic and immunogenic analysis of group A and group B respiratory syncytial virus G proteins expressed from recombinant baculoviruses - Sullender, Wayne M.; Britt, William J. (Journal of General Virology, 1996)
The attachment glycoprotein G plays a major role in the antigenic variability of respiratory syncytial (RS) virus. We have expressed from recombinant baculoviruses antigenic group A and group B RS virus G proteins (designated bacAG for the group A and bacBG for the group B virus G protein). The insect cell-produced G proteins migrated more rapidly in SDS-PAGE as compared to HEp-2 cell-derived G proteins owing to glycosylation differences. Antigenicity was tested by immunofluorescence; five of five group cross-reactive, five of six group A-specific, and six of six group B-specific MAbs reacted appropriately with bacAG and/or bacBG. In addition, bacAG and bacBG reacted with human polyclonal antibodies to RS virus. Cotton rats were immunized with bacAG, bacBG or a control lysate and challenged intranasally with a group A RS virus. The bacAG-immunized group had a statistically significant reduction in viral replication in the lungs (lung titres as mean log10 p.f.u./g ± sd, bacAG = 3.1 ± 1.2; control = 4.8 ± 0.6, P = 0.013). The bacBG-immunized group showed less reduction in viral titres (bacBG lung titres = 4.1 ± 0.6, P = 0.13 for bacBG compared to control). Thus, as expected, homologous protein (bacAG) immunization provided more protection against viral replication than immunization with the heterologous protein (bacBG). The G protein of RS virus expressed in insect cells had antigenic and immunogenic features which were similar to that of the G protein expressed in mammalian cells. The baculovirus-expressed G proteins should be useful for the study of immune responses to RS viruses.